Tingkat Pengetahuan Orang Tua tentang Pemeliharaan Kebersihan Gigi dan Mulut dengan Status Kebersihan Gigi dan Mulut Anak Berkebutuhan Khusus di SDLB Negeri Wiradesa Kabupaten Pekalongan - Ayu Wahyu Qomariyah; Prasko Prasko; Hermien Nugraheni (Jurnal Kesehatan Gigi, 2020)
In matters of dental and oral hygiene in children with special needs parents needed that they need depends on him. Parental knowledge is important to support oral and dental hygiene. The purpose of this study was to study the level of parental knowledge about dental and mouth maintenance with the dental and oral hygiene status of children with special needs in Wiradesa SDLB Negeri Pekalongan Regency. This type of research is quantitative descriptive, with cross sectional research methods. The population is 195 students. With a purposive sampling technique, with 48 respondents in grades 4 and 5, the measuring instruments in this study were the questionnaire and the examination sheet. Data obtained in the form of a cross tabulation table. Research carried out on 7 February 2020. The results showed that the average parent in Wiradesa SDLB had a medium level of knowledge and moderate OHI-S scores for children with a medium criterion. The conclusion obtained is about the knowledge of parents with greater oral and dental hygiene status caused by lack of parents' knowledge or information about how to care for dental and oral hygiene in children. Author for parents to increase knowledge about dental and mouth care, for school people to provide education for parents for the dental and oral health of children with special needs.